2018
DOI: 10.1108/jmtm-10-2017-0218
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid approach for quantifying supply chain risk and prioritizing the risk drivers

Abstract: Purpose The purpose of this paper is to identify various risk and sub-risk drivers that affect the supply chain (SC) performance and to propose a framework to quantify the overall SC risk index by considering the importance of each risk and sub-risk drivers and their mutual interactions. Design/methodology/approach A hybrid method based on decision-making trial and evaluation laboratory and analytical network process has been proposed to develop the risk quantification framework. A case study of Indian petro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 55 publications
0
30
0
1
Order By: Relevance
“…First, by reviewing the literature related to the research subject and using the theoretical principles of the research, the criteria of the project risks are identified and categorized. Accordingly, these criteria are categorized as follows: 1Project management criteria: estimation, planning, control, and communications (Mavi & Standing, ). 2Organizational criteria: project dependence, such as resources, budget, and prioritization (Ajayi & Oyedele, ). 3External criteria: suppliers, regulations, market, customers (Ershadi & Omidzadeh, ), and climate (in the environmental sense; Acharya et al., ). 4Technical criteria: requirements, technology, complexity, performance and reliability, and quality (Tarei, Thakkar, & Nag, ). …”
Section: Resultsmentioning
confidence: 99%
“…First, by reviewing the literature related to the research subject and using the theoretical principles of the research, the criteria of the project risks are identified and categorized. Accordingly, these criteria are categorized as follows: 1Project management criteria: estimation, planning, control, and communications (Mavi & Standing, ). 2Organizational criteria: project dependence, such as resources, budget, and prioritization (Ajayi & Oyedele, ). 3External criteria: suppliers, regulations, market, customers (Ershadi & Omidzadeh, ), and climate (in the environmental sense; Acharya et al., ). 4Technical criteria: requirements, technology, complexity, performance and reliability, and quality (Tarei, Thakkar, & Nag, ). …”
Section: Resultsmentioning
confidence: 99%
“…Various stages of SCRM process consist of identification, assessment, mitigation and control of risks (Hallikas et al, 2004). Risk classification and identification have been exhaustively discussed in the SCRM literature (Christopher and Peck, 2004;Wagner and Bode, 2008;Guertler and Spinler, 2015;Tarei et al, 2018). There is relatively less research that examines the effectiveness of alternative SCRM strategies in the different contextual environment (Chang et al, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The aforementioned challenges and issues involved in the PSC have attracted the global research attention in the past decade (Gardas et al, 2019;Tarei et al, 2018;Al-Qubaisi and Ajmal, 2018;Hussain and Khorramshahgol, 2016;Modarress et al, 2016;Lima et al, 2016;Shah et al, 2011). To the best of our knowledge, the existing literature is yet to deliver any published work focusing on the SC RM phase in the petroleum/oil and gas sector.…”
Section: Sc Risk Mitigation Strategies and Practicesmentioning
confidence: 99%
“…In the literature, supply chain risks are classified from various perspectives. Some researchers developed qualitative, quantitative or hybrid methods for identifying potential supply chain risks, such as supply chain vulnerability map (Trkman and McCormack, 2009;Malakouti et al, 2017;Tarei et al, 2018;Ramesh et al, 2019). Others focused on risk factor identification using the analytic hierarchy process method (Gaudenzi and Borghesi, 2006) and knowledge-based system approach.…”
Section: Risk Definition Matrixmentioning
confidence: 99%